The killing of African trypanosomes by ethidium bromide. - Arnab Roy Chowdhury (Public Library of Science (PLoS), 2010)
Introduced in the 1950s, ethidium bromide (EB) is still used as an anti-trypanosomal drug for African cattle although its mechanism of killing has been unclear and controversial. EB has long been known to cause loss of the mitochondrial genome, named kinetoplast DNA (kDNA), a giant network of interlocked minicircles and maxicircles. However, the existence of viable parasites lacking kDNA (dyskinetoplastic) led many to think that kDNA loss could not be the mechanism of killing. When recent studies indicated that kDNA is indeed essential in bloodstream trypanosomes and that dyskinetoplastic cells survive only if they have a compensating mutation in the nuclear genome, we investigated the effect of EB on kDNA and its replication. We here report some remarkable effects of EB. Using EM and other techniques, we found that binding of EB to network minicircles is low, probably because of their association with proteins that prevent helix unwinding. In contrast, covalently-closed minicircles that had been released from the network for replication bind EB extensively, causing them, after isolation, to become highly supertwisted and to develop regions of left-handed Z-DNA (without EB, these circles are fully relaxed). In vivo, EB causes helix distortion of free minicircles, preventing replication initiation and resulting in kDNA loss and cell death. Unexpectedly, EB also kills dyskinetoplastic trypanosomes, lacking kDNA, by inhibiting nuclear replication. Since the effect on kDNA occurs at a >10-fold lower EB concentration than that on nuclear DNA, we conclude that minicircle replication initiation is likely EB's most vulnerable target, but the effect on nuclear replication may also contribute to cell killing.